Islamic Republic of Mauritania : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
The report provides the details of the projections and estimates of Mauritania's gross domestic product by activity at current prices, 1992-2005 and at 1998 prices, 1993-2005; iron ore production, exports and stocks, consolidated government operations and revenue, 1994-2005; consumption of petroleum products, 1995-2005; monetary survey, foreign assets and liabilities of the banking system, assets and liabilities of the central bank and commercial banks, exports and imports, external publicly guaranteed debt outstanding and debt services, income and transfers, foreign trade indices, SNIM operating accounts and balance sheet, supply of cereals, et cetera.